Analytical management model for data-driven companies - Lima, José Jerônimo de Menezes; Redaelli, Emir José (Seven Editora, 2023)
This qualitative research proposes a management analytical model framework for data-driven companies. The framework was developed from the narrative review of the specialized literature on management models focused on data analysis to leverage the competitiveness of data-driven companies. An analytical management model is a set of logically interrelated management fundamentals, systemically integrated and coherent with an organizational philosophy based on data analysis for strategic decision-making, aiming to generate analytical advantage and, consequently, sustainable competitive advantage in business. The structure of the proposed framework has the following components: Analytical Competition and Analytical Advantage; Strategic Positioning and Analytical Focus; Transformative Leadership and Data-Driven Journey; Market Orientation and Trend Analysis; Domain of Data Science and Business Analytics; Data-Driven Decision Making; and Analytical Project Management. The main contribution of this research is of a theoretical-managerial nature and aims to identify determining factors for the ideation of a management model focused on data analysis. As future studies, the operationalization of the framework’s components is suggested, enabling its implementation in knowledge-intensive companies to validate its adequacy to the context of analytical competition. DOI:https://doi.org/10.56238/sevened2023.006-013